PENDAMPINGAN PEMASARAN PRODUK MAKANAN MELALUI PERANCANGAN BRAND IMAGE PRODUCT HOME INDUSTRY DI DESA TATAH PEMANGKIH KABUPATEN BANJAR - Basuki Basuki; Aida Vitria; Rahmi Widyanti (Universitas Islam kalimantan MAB, 2022)
The snack industry business has become the primary of food/snacks in people from other villages and is even favored by almost all people in the city. This training activity aims to help craftsmen or processors of the snack industry in growing creative thoughts / ideas to produce other products in order to be able to compete with other products in the face of competition. It is hoped that this training can make the snack industry survive and compete with the increasing number of modern food products. The problem faced by the snack food industry maker is that the food industry is very much influenced by the proliferation of other food industries. Therefore, the growing demand for food products continues to demand high creativity and product innovation. The fact that there is a variety of products, so as not to cause saturation from consumers. In addition to the level of discipline of food industry makers, apart from demanding food industry processing skills to read market opportunities and develop marketing areas, skills are also needed to design a product brand image.